TSAGARI, Dina. FLOROS, Georgius. Translation in Language Teaching and Assessment. Cambridge: Cambridge Scholars Publishing, 2013. - Rita Ferreira Arcenio (Cadernos de Tradução)
TSAGARI, Dina. FLOROS, Georgius. Translation in Language Teaching and Assessment. Cambridge: Cambridge Scholars Publishing, 2013.